The simultaneous administration of microplastics and cadmium alters rat testicular activity and changes the expression of PTMA, DAAM1 and PREP - Venditti, Massimo; Ben Hadj Hassine, Majida; Messaoudi, Imed; Minucci, Sergio (Frontiers in Cell and Developmental Biology, 2023)
This paper confirms the damaging effects produced by MPs and Cd on the rat testicular activity. Oral treatment with both chemicals caused testicular damage, that has been documented by biomolecular and histological alterations, namely impaired morphometric parameters, increased apoptosis, reduced testosterone synthesis and down-regulation of the of steroidogenic enzyme 3β-HSD. We further demonstrated, for the first time, that both MPs and Cd can affect the protein level of PTMA, a small peptide regulating the proliferation and differentiation of germ cell. Interestingly, also the cytoarchitecture of testicular cells was perturbed by the treatments, as evidenced by the impaired expression and localization of DAAM1 and PREP, two cytoskeleton-associated proteins involved in the differentiation of germ cells into spermatozoa, altering the normal spermatogenesis. Finally, we showed that the effect of the simultaneous treatment with MPs and Cd were more severe than those produced by MPs alone and less harmful than those of Cd alone. This could be due to the different ways of exposure of the two substances to rats (in drinking water for Cd and in oral gavage for MPs), since being their first contact in the gastrointestinal tract of the animals, MPs may adsorb Cd, reducing its bioavailability via the Trojan-horse effect.